Flow cytometry-based method using diversity of cytokine production differentiates between Mycobacterium tuberculosis infection and disease - Dolezalova, Karolina; Hadlova, Petra; Ibrahimova, Marketa; Golias, Jaroslav; Baca, Lubos; Kopecka, Emilia; Sukholytka, Mariia; Koziar Vasakova, Martina (Tuberculosis (Edinburgh, Scotland), 2024)
Authors present a pilot study of the development of innovative flow cytometry-based assay with a potential for use in tuberculosis diagnostics. Currently available tests do not provide robust discrimination between latent tuberculosis infection (TBI) and tuberculosis disease (TB). The desired application is to distinguish between the two conditions by evaluating the production of a combination of three cytokines: IL-2 (interleukin-2), IFNɣ (interferon gamma) and TNFɑ (tumor necrosis factor alpha) in CD4+ and CD8+ T cells. The study was conducted on 68 participants, divided into two arms according to age (paediatric and adults). Each arm was further split into three categories (non-infection (NI), TBI, TB) based on the immune reaction to Mycobacterium tuberculosis (M.tb) after a close contact with pulmonary TB. Each blood sample was stimulated with specific M.tb antigens present in QuantiFERON tubes (TB1 and TB2). We inferred TBI or TB based on the predominant cytokine response of the CD4+ and/or CD8+ T cells. Significant differences were detected between the NI, TBI and the TB groups in TB1 in the CD4+TNFɑ+parameter in children. Along with IL-2, TNFɑ seems to be the most promising diagnostic marker in both CD4+and CD8+ T cells. However, more detailed analyses on larger cohorts are needed to confirm the observed tendencies.
Keywords: diferenciální diagnóza; CD4-Positive T-Lymphocytes; průtoková cytometrie; Flow cytometry-based assay; TB infection; senioři; lidé středního věku; Interleukin-2; TB disease; Latent Tuberculosis; mladý dospělý; Female; Humans; dospělí; test pomocí interferonu gama; Aged; Male; Child; ženské pohlaví; Pilot Projects; předškolní dítě; Biomarkers; Diagnosis, Differential; CD8-pozitivní T-lymfocyty; Middle Aged; Interferon-gamma Release Tests; Young Adult; Predictive Value of Tests; Tuberculin Test; biologické markery; mladiství; lidé; Interferon gamma release assay (IGRA); Tumor Necrosis Factor-alpha; Mycobacterium tuberculosis; Flow Cytometry; TB immunity; Feasibility Studies; Interferon-gamma; Prospective Studies; Tuberculosis, Pulmonary; kojenec; mužské pohlaví; interleukin-2; Child, Preschool; prospektivní studie; TNF-alfa; dítě; interferon gama; plicní tuberkulóza; pilotní projekty; Adolescent; Adult; CD8-Positive T-Lymphocytes; prediktivní hodnota testů; tuberkulinový test; CD4-pozitivní T-lymfocyty; studie proveditelnosti; Infant; latentní tuberkulóza